All Days 2008
DOI: 10.2118/114050-ms
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of an Underbalanced Drilling Operation Utilizing Supercritical Carbon Dioxide

Abstract: Mechanistic modeling of an underbalanced drilling operation using carbon dioxide has been developed in this research. The use of carbon dioxide in an underbalanced drilling operation eliminates some of the operational difficulties inherent with gaseous drilling fluids, such as generating enough torque to run a downhole motor. The unique properties of CO2, both inside the drill pipe and the annulus are shown in terms of optimizing the drilling operation by achieving a low bottom hole pressure window. Typically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Due to its unique properties and the relatively easy critical conditions which need to be obtained, SC-CO 2 fluid has been widely studied and used in numerous fields [3][4][5][6]. In recent years, SC-CO 2 fluid, which has many advantages for improving the rates of penetration and single well recovery, has been applied in the field of drilling and completion engineering, especially for the exploitation of unconventional reservoirs [7][8][9][10]. Moreover, it is reported that a SC-CO 2 jet has better rock erosion and fracturing capacity than a water jet does, thus, it has been widely considered as a promising and novel jet technology [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its unique properties and the relatively easy critical conditions which need to be obtained, SC-CO 2 fluid has been widely studied and used in numerous fields [3][4][5][6]. In recent years, SC-CO 2 fluid, which has many advantages for improving the rates of penetration and single well recovery, has been applied in the field of drilling and completion engineering, especially for the exploitation of unconventional reservoirs [7][8][9][10]. Moreover, it is reported that a SC-CO 2 jet has better rock erosion and fracturing capacity than a water jet does, thus, it has been widely considered as a promising and novel jet technology [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The first indoor test conducted in the United States (US) in 2000 proved that the efficiency of SC-CO 2 jets for Mancos shale breaking is 3.3 times greater than that of water jets, and that the energy per unit volume is 20% of that of water jets (Kolle, CONTACT Hongjian Ni 724119710@qq.com 2000; Kolle & Marvin, 2000). In the current work, the feasibility of both coiled tubing and underbalanced drilling by SC-CO 2 is analyzed (Al-Adwani, 2007;Gupta, Gupta, & Langlinais, 2005). In order to better understand rock-breaking mechanisms, Chinese researchers carried out systematic experiments and theoretical studies on the rock-breaking properties of SC-CO 2 .…”
Section: Introductionmentioning
confidence: 96%
“…[2]. It has many unique properties, such as high density, high diffusivity, low viscosity, high absorptive capacity by rock substances and so on, which make SC-CO 2 very suitable for the exploitation of oil and gas reservoirs as a working fluid [3][4][5][6]. In more specific terms, high density can provide enough power for downhole drilling tools.…”
Section: Introductionmentioning
confidence: 99%